Hypotheses about Édouard glissant’s preface notion - Alves, Alcione Correa (2022)
this text aims to set initial lines for an apropriation of the premise of the Caribbean as a preface to the Americas, according to the essay Introduction à une poétique du Divers, by Édouard Glissant, understanding it in a frame of American black thought. The apropriation of Glissant’s premiseaims to propose bases for a methodological tool, based on the epistemological centrality of the place, subsidizing literary analyzes among a corpus of Afro-American literatures. This text, initially, starts from the hypothesis that any African-American national literature (including Afro-Brazilian literature) can be taken, in a sparing way, as a preface to a broader corpus of African-American literature.